The returns of IHSG, NIKKEI and NASDAQ during COVID-19 pandemic - Christina Rengkung; Devina Polii; Gratia N. Sembel; Myline Rau (The Contrarian : Finance, Accounting, and Business Research, 2022)
The Covid-19 pandemic has had quite an unfavorable impact, especially on the market return performance of the IHSG, NIKKEI, and NASDAQ. This study aims to analyze the relationship and differences in market return performance in the IHSG, NIKKEI, and NASDAQ in the period from March 3, 2020, to March 3, 2021. This study finds that market returns from the three markets have a positive and significant relationship. Moreover, this study also found that the three markets had the same market return performance during the Covid-19 pandemic.